Automated diagnostic tool for hypertension using convolutional neural network - Soh, Desmond Chuang Kiat (2021)
Background: Hypertension (HPT) occurs when there is increase in blood pressure (BP) within the arteries, causing the heart to pump harder against a higher afterload to deliver oxygenated blood to other parts of the body.